Validity and reliability of the Moxy oxygen monitor during incremental cycling exercise - Crum, E. M.; O'Connor, W. J.; Van Loo, L.; Valckx, M.; Stannard, S. R. (European Journal of Sport Science, 2017)
Introduction: The Moxy is a novel, cutaneously placed muscle oxygen monitor which claims to measure local oxygen saturation (SmO2) and total haemoglobin (THb) using near-infrared spectroscopy. If shown to be reliable, its data storage and telemetric capability will be useful for assessing localised O2 usage during field-based exercise. This study investigated the reliability of the Moxy during cycling and assessed the correlations between its measurements, whole-body O2 consumption (VO2) and heart rate (HR). Methods: Ten highly trained cyclists performed an incremental, step-wise cycling protocol on two occasions while wearing the Moxy. SmO2, THb, VO2 and HR were recorded in the final minute of each five-minute stage. Data were analysed using Spearman`s Order-Rank Coefficient (SROC), Intraclass Correlation (ICC), and Coefficient of Variance (COV). Significance was set at p = .05. Results: SmO2 showed a `strong` or `very large` correlation between trials (SROC: r = 0.842-0.993, ICC: r = 0.773-0.992, p = .01) and was moderately correlated with VO2 and HR (r = -0.71-0.73, p = .01). SmO2 showed a moderate to high reliability at low intensities, but this decreased as relative exercise intensity increased. THb showed poor correlations between tests and with the other measured variables, but was highly reliable at all power outputs. Conclusions: The Moxy is a reliable device to measure SmO2 at low to moderate intensities, but at higher intensities, greater variation in measurements occurs, likely due to tissue ischaemia or increased movement artefacts due to more frequent muscular contractions. THb has low variation during exercise, and does not appear to be a valid indicator of muscle oxygenation.